2005
DOI: 10.1128/jcm.43.3.1246-1250.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Virulence Plasmids and Serotyping of Rhodococcus equi Isolates from Submaxillary Lymph Nodes of Pigs in Hungary

Abstract: The plasmid types and serotypes of 164 Rhodococcus equi strains obtained from submaxillary lymph nodes of swine from different piggeries in 28 villages and towns located throughout the country were examined. The strains were tested by PCR for the presence of 15-to 17-kDa virulence-associated protein antigen (VapA) and 20-kDa virulence-associated protein antigen (VapB) genes. R. equi is an aerobic, gram-positive coccobacillus which frequently causes chronic suppurative bronchopneumonia with abscesses, lymphaden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
47
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 23 publications
4
47
0
4
Order By: Relevance
“…The studies on this topic report conflicting results: some authors recovered R. equi from the lymph nodes of healthy pigs (Takai et al, 1996;Madarame et al, 1998;Dvorska et al, 1999;Makrai et al, 2005) while others reported the isolation of R. equi almost exclusively from lymph nodes with granulomatous lesions, identifying it as the causative agent of lymphadenitis in pigs (Komijn et al, 2007). In the scope of one study, R. equi was found in pigs with and without caseous lymphadenitis, but the isolation rate was reported to be five times higher in the lymph nodes with lesions (Katsumi et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies on this topic report conflicting results: some authors recovered R. equi from the lymph nodes of healthy pigs (Takai et al, 1996;Madarame et al, 1998;Dvorska et al, 1999;Makrai et al, 2005) while others reported the isolation of R. equi almost exclusively from lymph nodes with granulomatous lesions, identifying it as the causative agent of lymphadenitis in pigs (Komijn et al, 2007). In the scope of one study, R. equi was found in pigs with and without caseous lymphadenitis, but the isolation rate was reported to be five times higher in the lymph nodes with lesions (Katsumi et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Takai and Tsubaki (1985) and Takai et al (1996) found R. equi in 21.7% and 3.1% of investigated submaxillary lymph nodes of apparently healthy pigs, respectively. Recently, an isolation rate of 14.0% was reported from swine submaxillary lymph nodes without macroscopic lesions in Hungary (Makrai et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We isolated R. equi from the lymph nodes with NANAT agar plates as described (Takai et al, 1996). Strain ATCC 33701 and 27 representative strains of intermediate virulence were used as reference strains because their plasmid characteristics and virulence levels have been described (Takai et al, 1996(Takai et al, , 2003Fukunaga et al, 1999;Makrai et al, 2005Makrai et al, , 2008. Plasmid profiles and the presence of vapA and vapB genes were determined by PCR as described (Makrai et al, 2008), and serum samples of wild boars were analyzed for anti-R. equi-specific antibodies by western blotting (Takai et al, 1991) with anti-pig immunoglobulin antibodies conjugated to horseradish peroxidase (Cappel Laboratories, Richmond, California, USA).…”
mentioning
confidence: 99%